1988
DOI: 10.1002/pssb.2221480138
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Infrared Transmission Spectra of Thin Insulating Films

Abstract: Dedicat.ed to Prof. Dr. E. GUTSCHE on the occasion of his 60th birthday It will be demonstrated that the so-called LO-TO splittings in the infrared spectra of thin amorphous insulating layers are a consequence of boundary conditions. Es wird gezeigt, daB die sogenannten LO-TO-Aufspaltungen in IR-Spektren dunner amorphcrIsolatorschichten aus Randbedingungen folgen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 8 publications
5
17
0
Order By: Relevance
“…This conclusion is in agreement with results of Ref. [29] where the appearance of the LO component of the IR spectra was explained on the basis of the consideration of the boundary conditions as a result of the space restriction of the condensed media in the direction of the longitudinal vibrations. Therefore, there are a grounds for the assumption that the absorption on the ν LO frequency may be found in liquids also.…”
Section: Resultssupporting
confidence: 82%
“…This conclusion is in agreement with results of Ref. [29] where the appearance of the LO component of the IR spectra was explained on the basis of the consideration of the boundary conditions as a result of the space restriction of the condensed media in the direction of the longitudinal vibrations. Therefore, there are a grounds for the assumption that the absorption on the ν LO frequency may be found in liquids also.…”
Section: Resultssupporting
confidence: 82%
“…A similar conclusion also follows from the theoretical work of Lechman 19 , who demonstrated that the appearance of absorption at the frequency of LO vibrations in structure-less dielectrics is a result of the boundary conditions arising in thin films at an oblique incidence of light. Thus, we can conclude that the case of 1D size confinement is apparent in the reflection-absorption spectra (RAS) of thin dielectric films independent of their structure.…”
Section: Discussionsupporting
confidence: 71%
“…We conclude that the absorption bands, observed earlier and ascribed to the Berreman effect (Berreman, 1963), are a particular case of the manifestation of 1D confinement. This conclusion is supported by a study by (Lehmann, 1988), where it was shown that the appearance of the absorption band at the frequency of the LO-phonons in an amorphous dielectric is a consequence of the boundary conditions in a dielectric film at an oblique incidence of the probe beam. The numerical and experimental results described above indicate that relatively large spectral effects can be expected as a result of dielectric confinement.…”
Section: Discussionmentioning
confidence: 56%
“…The absorption spectra of the amorphous media at frequencies ν l has already been discussed in numerous papers (Berreman, 1963;Röseler, 2005;Tolstoy et al, 2003;Iglesias et al, 1990;DeLeeuw & Thorpe, 1985). Conclusions on the size dependent nature of this effect have been made earlier in the theoretical work of (Lehmann, 1988). We would like to emphasise that we obviously cannot discuss LO-phonons in amorphous solids and, in particular, in liquids, since the new bands observed arise as a result of the interaction of the transverse electromagnetic wave with a condensed medium under dielectric confinement, when the contribution from surface vibrations becomes greater than that from the bulk.…”
Section: Theoretical Considerationsmentioning
confidence: 89%